Organic room-temperature phosphorescence materials for bioimaging. Issue 36 (11th April 2023) - Zhang, Yahui; Li, Hairong; Yang, Mengdie; Dai, Wenbo; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; Wang, Zhouyu; Dong, Yuping; Yu, Xiaoqi
Abstract : Organic room-temperature phosphorescence (RTP) materials are currently the focus of research in the field of bioimaging. High performance of RTP materials and optimization in the preparation process of RTP nanoparticles are both important. Abstract : Organic room-temperature phosphorescence (RTP) materials are currently the focus of research in the field of bioimaging. In comparison with the conventional imaging modalities based on organic fluorescent dyes, RTP materials with long lifetime enable time-resolved imaging to improve the imaging resolution by avoiding autofluorescence. In this review, we will start with summarizing strategies for achieving high performance RTP materials for bioimaging, including the development of RTP-compounds, host–guest doping materials, and supramolecular assemblies. We then discuss the optimization of nanonization processes to obtain RTP nanoparticles with controllable size, high dispersibility, and improved stability. The differences between top-down and bottom-up approaches are further described. Finally, we briefly introduce the emerging methods for preparing RTP materials for bioimaging.